2003
DOI: 10.1016/s0022-0248(02)02223-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-stress GaN epitaxial layers grown on Si(111) by using a porous GaN interlayer converted from GaAs

Abstract: This paper reports the reduced-stress GaN epitaxial growth on Si (1 1 1) using a porous GaN interlayer which is formed from GaAs layer by a novel nitridation process. Initially a 2 μm thick GaAs layer is grown on a Si(1 1 1) substrate by MBE. Then, a GaN buffer layer of 20 nm thick is grown on the GaAs layer at 550°C in a MOVPE reactor. The GaAs layer capped with the GaN buffer layer is annealed in NH3 to 1000°C. Through this process, a porous GaN layer is formed beneath the GaN cap layer. An epitaxial GaN lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…It was found in previous work that use of porous substrates can lead to significant strain relaxation in the film, at least in certain cases [20] [21].…”
Section: Film Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found in previous work that use of porous substrates can lead to significant strain relaxation in the film, at least in certain cases [20] [21].…”
Section: Film Strainmentioning
confidence: 99%
“…This conclusion is, perhaps, not surprising when we carefully consider the geometry of the situation. The prior work which did observe a strain reduction was for GaN growth on porous GaN, employing a GaN buffer layer that was then etched to make it porous [20] [21]. It was found that the pores extended vertically down into the layer, i.e.…”
Section: Film Strainmentioning
confidence: 99%
“…GaAs has a lower yield strength than GaN, sapphire and Si, so cracking and plastic deformations or defects are more likely to occur in the GaAs layer rather than GaN epilayer [4]. In our past study, due to the formation of a porous GaN interlayer by novel nitridation of a 2 µm GaAs layer on Si(111), a crack free GaN epilayer was found to be grown over the interlayer and high intense excitonic emission intensity was obtained from the epilayer [5]. But in that study, the effect of GaAs layer thickness deposited on Si(111) and its nitridation impact on the optical properties of the GaN epilayers had not been focussed.…”
mentioning
confidence: 89%
“…But in that study, the effect of GaAs layer thickness deposited on Si(111) and its nitridation impact on the optical properties of the GaN epilayers had not been focussed. Nitrogen has a certain diffusion length, so the novel nitridation [5] of different thickness GaAs layers and a study on the epilayer stress effect on cracking and optical properties are interesting issues. The near band edge luminescence intensity of GaN epilayers increases with decreasing stress and defects [3].…”
mentioning
confidence: 99%
“…Therefore, crack generation becomes a serious problem in this case. In order to solve such problems, various growth techniques, ELOG [1], ABLOG [2], and porous interlayer formation [3] have been studied. A significant reduction of residual stress as well as improvement in the quality of epitaxial GaN grown on sapphire is attained by using isoelectronic In doping [4][5][6].…”
Section: Introductionmentioning
confidence: 99%